Psycho - social empowerment education based on choice theory in high - risk behaviors and hopeful of adolescent girls: Development and evaluation of efficacy - Shirin Valizadeh; Esmaeil Sadipour; Fariborz Dortaj; Ali Delavar; Kamran Sheivandi Cholicheh (مجله علوم روانشناختی, 2022)
Background: Adolescence is one of the most sensitive periods of life, which plays a fundamental role in the success or failure of individuals in the future. In this regard, high - risk behaviors that are becoming more common in these ages are also needed, and hope for the future will be strengthened in juveniles too. Aims: The aim of this study was to develop and examine the efficacy of psycho - social empowerment education based on choice theory in high - risk behaviors and hopes of adolescent girls. Methods: In the form of a pretest-posttest- follow-up with control group quasi-experimental design, 30 students of adolscent girls from 2 region of education and teaching of Tehran were selected and were assigned randomly in two expreimental (15 subjects) and control (15 subjects) groups. Data collection tools include the risk questionnaire of Iranian teenagers (Zadehmohammadi et al., 2012) and the hope questionnaire (Schneider et al., 2016). The educational package of psychosocial empowerment based on choice theory, after development, was applied during eight-nighnteety minute’s sessions. Mixed analysis of varinace was used to analyze the data. Results: The results indicated that the education of psycho - social empowerment based on choice theory results in decreasing high-risk behaviors (F= 4.036; P= 0.001) of adolescent girls and has a positive effect on hope (F= 4.791; P= 0.001). Conclusion: training of psychosocial competencies based on choice theory can affect the level of high - risk and hopeful behavior in adolescent girls and is recommended alongside other treatments